Lettura e dispersione - Dora Maria Scierri, Irene (Processi e linguaggi dell'apprendimento - Open Access, 2018)
Reading and dispersion constitute, in different ways, two crucial points of scholastic reality and of educational research. This book highlights the multiple cognitive and emotional effects of reading and, more generally, the different ways to prevent and combat school dropouts. Therefore the volume has a double interest: on the one hand, to help the understanding of the school dispersion and the perception that it has in the field; on the other hand, identify effective prevention and recovery interventions, with particular attention to reading aloud and narrative orientation.